Incorporating blood-based liquid biopsy information into cancer staging: time for a TNMB system?. (5th December 2017) - Yang, M; Forbes, M E; Bitting, R L; O'Neill, S S; Chou, P -C; Topaloglu, U; Miller, L D; Hawkins, G A; Grant, S C; DeYoung, B R; Petty, W J; Chen, K; et al.
Abstract: Tissue biopsy is the standard diagnostic procedure for cancer. Biopsy may also provide material for genotyping, which can assist in the diagnosis and selection of targeted therapies but may fall short in cases of inadequate sampling, particularly from highly heterogeneous tumors. Traditional tissue biopsy suffers greater limitations in its prognostic capability over the course of disease, most obviously as an invasive procedure with potential complications, but also with respect to probable tumor clonal evolution and metastasis over time from initial biopsy evaluation. Recent work highlights circulating tumor DNA (ctDNA) present in the blood as a supplemental, or perhaps an alternative, source of DNA to identify the clinically relevant cancer mutational landscape. Indeed, this noninvasive approach may facilitate repeated monitoring of disease progression and treatment response, serving as a means to guide targeted therapies based on detected actionable mutations in patients with advanced or metastatic solid tumors. Notably, ctDNA is heralding a revolution in the range of genomic profiling and molecular mechanisms to be utilized in the battle against cancer. This review will discuss the biology of ctDNA, current methods of detection and potential applications of this information in tumor diagnosis, treatment, and disease prognosis. Conventional classification of tumors to describe cancer stage follow the TNM notation system, heavily weighting local tumor extent (T), lymph node invasion (N), and detectable metastasis (M). With recent advancements in genomics and bioinformatics, it is conceivable that routine analysis of ctDNA from liquid biopsy (B) may make cancer diagnosis, treatment, and prognosis more accurate for individual patients. We put forward the futuristic concept of TNMB tumor classification, opening a new horizon for precision medicine with the hope of creating better outcomes for cancer patients.